The Task of a Naturalist: An Epitaph for Philippa Foot (1920-2010) - Makowski, Piotr (ETHICS IN PROGRESS, 2010)
Philippa Foot once said: I'm not clever at all. I have a certain insight into philosophy, cost I think. But I'm not clever, I don't find complicated arguments easy to follow(Baggini, 2003). Foot's cleverness enticed many thinkers to take these Gombrowiczian lines seriously.